2009
DOI: 10.1093/molehr/gap045
|View full text |Cite
|
Sign up to set email alerts
|

Differential actions of estrogen and SERMs in regulation of the actin cytoskeleton of endometrial cells

Abstract: Estrogen and selective estrogen receptor modulators (SERMs) differentially impact endometrial cell function, however, the biological basis of these differences is not established. Deregulated cell adhesion to the extracellular matrix, cell movement and invasion are related to endometrial disorders, such as endometriosis or endometrial cancer. Remodeling of the actin cytoskeleton is required to achieve cell adhesion and movement. Estrogen receptor (ER) regulates actin and cell membrane remodeling through extra-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 37 publications
2
38
0
1
Order By: Relevance
“…Moesin is constitutively activated by phosphorylation of threonine 555 [20] and the activation of ERM family members links actin filaments to CD43, CD44, and ICAM-1 which are involved in adhesion [21]. Moesin is critical for invasion in 3D matrices [22], and phosphorylation of moesin has also been linked with invasion in endometrial cells [23]. The alterations in MSN and RDX, observed in the dasatinib-treated WM-115 cells, may play a role in the effects of dasatinib on migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Moesin is constitutively activated by phosphorylation of threonine 555 [20] and the activation of ERM family members links actin filaments to CD43, CD44, and ICAM-1 which are involved in adhesion [21]. Moesin is critical for invasion in 3D matrices [22], and phosphorylation of moesin has also been linked with invasion in endometrial cells [23]. The alterations in MSN and RDX, observed in the dasatinib-treated WM-115 cells, may play a role in the effects of dasatinib on migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of estradiol (E 2 ) on reproductive tract structure and function are well known. Recently, however, studies have indicated a role for E 2 in tumor initiation and progression through its promotion of the proliferative, migratory and invasive capabilities of cells (2)(3)(4)(5)(6). Many of the changes that occur in the endometrium during tumorigenesis are similar to those observed during implantation.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogens regulate several cytoskeletal components, particularly actin fibers (9)(10)(11). Through the control of actin organization, E regulates cell morphology and interaction with ECM and drives cell movement (9)(10)(11).…”
mentioning
confidence: 99%
“…Through the control of actin organization, E regulates cell morphology and interaction with ECM and drives cell movement (9)(10)(11).…”
mentioning
confidence: 99%